(untitled) (APPLICATION: Applied science in Learning Research, 2023)
ABSTRACT The development of increasingly sophisticated technology has become an important means of achieving more effective and efficient educational goals. But behind that, there is a big demand for lecturers/teachers to develop skills in mastering technology and learning media. So it is necessary to develop learning media using the wizer.me application. The aims of this study are: 1) to describe the results of HOTS-based interactive worksheet validation using wizer.me media on ecosystem material according to media experts; 2) Describe the results of HOTS-based interactive worksheet validation using media wizer.me on ecosystem materials according to material experts. This research method is development using the ADDIE model. The instrument used was a validation questionnaire for media experts and material experts. Data analysis techniques in the form of validation and suggestions from the validator. The validation results from media experts showed that 82% were declared very feasible and the validation results from material experts showed 72.7% were declared feasible, indicating that wizer.me learning media on ecosystem material is suitable for use as a medium for learning ecosystem biology material. Keywords: Ecosystem, HOTS, Wier.Me, Worksheet.